Peran Kepala Madrasah dalam Mengelola Institusi Pendidikan Islam - Sholeh, Agus (CV Kalimasada Group, 2024)
The role of the madrasah principal in Islamic educational institutions is very important in managing various expected goals and targets. As the highest leader, the madrasah principal has a standard of eligibility within himself to succeed in various constructive policies in education. This study aims to analyze the role of the madrasah principal in managing educational institutions, both within the school and externally. The researcher used qualitative research with the type of literature study from various sources, including books, journals, academic research results, and other reports. The study results indicate that the madrasah principal must have four main roles in developing Islamic education, namely as an administrator, as supervisor, as curriculum and human resource manager, and as manager of facilities and infrastructure and information technology. For this reason, this study can be used as an important reference in understanding the role of Islamic leadership through madrasah education.